Predictors of activity and participation across neurodegenerative conditions: a comparison of people with motor neurone disease, multiple sclerosis and Parkinson’s disease - Morley, D; Dummett, S; Kelly, L; Fitzpatrick, R; Jenkinson, C (BioMed Central, 2018)
Background: Comparisons between neurological conditions have the potential to inform service providers by identifying particular areas of difficulty experienced by affected individuals. This study aimed to identify predictors of activity and participation in people with motor neurone disease (MND), people with multiple sclerosis (MS) and people with Parkinson’s Disease (PD). Methods: The Oxford Participation and Activities Questionnaire (Ox-PAQ) and Medical Outcomes Study 36-Item Short Form Survey (MOS SF-36) were administered by postal survey to 386 people with a confirmed diagnosis of MND, MS or PD. Data analyses focused on stepwise regression analyses in order to identify predictors of activity and participation in the three conditions assessed. Results: Three hundred and thirty four participants completed the survey, a response rate of 86.5%. Regression analyses identified multiple predictors of activity and participation dependent on Ox-PAQ domain and disease group, the most prominent being social and physical functioning as measured by the MOS SF-36. Conclusions: Results indicate that the physical and social consequences of neurological illness are of greatest relevance to people experiencing the conditions assessed. Whilst the largely inevitable physical implications of disease take hold, emphasis should be placed on the avoidance of social withdrawal and isolation, and the maintenance of social engagement should become a significant priority.